EFFICIENCY AND COMMODITY COMPETITIVENESS ANALYSIS OF INTEGRATED BEEF CATTLE, RICE, AND MAIZE FARMING ON SUBOPTIMAL LAND IN MINAHASA REGENCY - Jolyanis Lainawa; Eusebius K.M. Endoh; Zadrak M. Warouw (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
This study aims to analyze the efficiency, competitiveness, constraints-opportunities, and strategic position of an integrated farming system combining beef cattle, rice, and maize on suboptimal land in Minahasa Regency. Suboptimal land characteristics such as low pH, poor drainage, and low soil fertility require efficient and innovative farming approaches. Integrated farming systems offer a solution by integrating crop and livestock sub-systems in a single business unit that supports each other and utilizes resources optimally. The methods used include data envelopment analysis (DEA) and stochastic frontier analysis (SFA) approaches to measure technical and economic efficiency, and policy analysis matrix (PAM) to evaluate competitiveness. The results showed high technical and economic efficiency, with efficiency values above 0.80, and private cost ratio (PCR) and domestic resource cost ratio (DRCR) values < 1. This indicates the feasibility of the business privately and socially without any policy distortions. Factors that support efficiency include the use of crop waste as animal feed and livestock waste as organic fertilizer, as well as income diversification that reduces business risk. However, challenges such as high start-up costs, limited market access, and suboptimal production technology are still obstacles. Based on the SWOT analysis and IE Matrix, the system is in the “grow and develop” strategy position, showing great potential for development. Thus, this system is worthy of being used as a model for sustainable agricultural development based on high efficiency and competitiveness.